Clinical Characteristics and Risk Factors for Seizures to Recur in Calcified Neurocysticercosis: Prospective Cohort Study - Archana Verma; Alok Kumar; Divyata Sachan (Acta Neurologica Taiwanica)
Aim: Calcification of degenerating neurocysticercosis (NCC) is common and likely to occur late in the degenerative process and is important for seizure foci. The present study was aimed at identifying the clinical and radiological variables associated with seizure recurrence in people with single or multiple calcified NCC lesions. Material and Methods: We evaluated 85 adult patients with calcified NCC lesions for recurrence of seizures during the follow-up period of one year. Results: The mean age of the study population was 24.49 ± 9.17 years. Nocturnal seizures were present in 43.5% and serial seizures in 42.4%. A single calcified lesion was present in 61 (71.8%), and perifocal oedema surrounding the calcified lesions was present in 38 (44.7%). Recurrence of seizures was noted in 37 (43.5%) of the cases. On multivariate analysis, the factors that were significantly associated with the recurrence of seizures were: nocturnal seizures [OR: 0.054 (0.015–0.199)], serial seizures [OR: 0.141 (0.041–0.485)], and perifocal oedema [OR: 0.031 (0.008–0.129)]. Conclusion: In our study, serial seizures, nocturnal seizures, and perifocal oedema were linked with the recurrence of seizures in calcified NCC lesions. Perilesional oedema should be treated aggressively with anti-inflammatory/immunosuppressive therapy as well as with anti-seizure medication.